(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Saliva plays a crucial role in maintaining oral homeostasis, including mechanical cleansing, buffering capacity, remineralization, and antimicrobial defense. In children with chronic kidney disease (CKD) undergoing hemodialysis, systemic disturbances significantly affect salivary function and composition, contributing to the development of oral diseases.